Mapping brain activity and neurotransmitters pre-cigarette smoking evolution: A study of male subjects - Sun, Jieping; zhang, Mengzhe; Dang, Jinghan; Niu, Xiaoyu; Tao, Qiuying; Kang, Yimeng; Ma, Longyao; Mei, Bohui; Wei, Yarui; Wang, Weijian; Han, Shaoqiang; Cheng, Jingliang; et al. (Journal of psychiatric research, 2024)
The impact of tobacco smoking on global health persists and it is essential to understand the progression of addiction and the involvement of neurotransmitters. This study assessed 47 participants with tobacco use disorder (TUD) categorized based on changes in Fagerström Test for Nicotine Dependence (FTND) scores over 6 years: progressive TUD (pTUD), regressive TUD (rTUD), and stable TUD (sTUD). Additionally, 35 healthy controls were included. Resting-state functional magnetic resonance imaging was used to evaluate brain regional homogeneity (ReHo) and correlations with neurotransmitter distributions using JuSpace. Significant differences in ReHo were observed among pTUD, rTUD, sTUD, and controls. After strict Bonferroni correction, rTUD exhibited increased ReHo in the dorsolateral superior frontal gyrus compared to sTUD (p < 0.001) and controls (p < 0.001). Both pTUD (p < 0.001) and rTUD (p < 0.001) showed decreased ReHo in the superior temporal gyrus compared to sTUD. sTUD had increased ReHo in the supramarginal gyrus compared to all other groups (p < 0.001, p < 0.001, p = 0.002, separately). The strongest association, which survived rigorous Bonferroni correction, was between the ReHo changes in rTUD compared to sTUD and neurotransmitter distribution. This includes 5-hydroxytryptamine receptor 2A (p = 0.001), gamma-aminobutyric acid type A receptor (p < 0.001), norepinephrine transporter (p < 0.001), and N-Methyl-D-Aspartate (p = 0.002). This study provides insights into how smoking behaviors correlate with alterations in brain activity and neurotransmitter function. By elucidating these neural links to tobacco use disorder progression, our findings contribute to a deeper understanding of smoking's neurological impact and potentially inform more targeted therapeutic strategies. •Subjects categorized by 6-year FTND changes: progressive, regressive, stable TUD.•Brain ReHo patterns vary across stable, progressive, regressive TUD and controls.•Correlations link neurotransmitter variations to ReHo changes.